Tibial-Sling Triangular Medial Collateral Ligament Reconstruction With Posterior Oblique Ligament Limb - Carlos E. Franciozi MD, PhD; Enzo S. Mameri MD, MSc; Guilherme C. Gracitelli MD, PhD; Felipe C. Schumacher MD; Marcos V. Credidio MD; Sérgio Canuto MD; Marcelo S. Kubota MD (SAGE Publishing, 2023)
Background: While most medial-sided knee injuries can be managed conservatively, high-grade injuries of the posteromedial corner have been reported to have less than optimal outcomes with conservative approaches, resulting in residual valgus and rotational instability. Consensus among experts postulates that treatment should be based on reconstructing both the superficial medial collateral ligament (sMCL) and the posterior oblique ligament (POL). We present a modified technique of a tibial-sling anatomic MCL reconstruction with a POL limb. Indications: High-grade injuries of the posteromedial corner, specifically injuries with medial joint gapping in extension or grade 3 medial-sided tears. Technique Description: The MCL is reconstructed with a semitendinosus autograft in a tibial sling, created by converging perpendicular bone tunnels at its anatomic tibial insertion, and fixed to a femoral tunnel in the isometric point just posterior and proximal to the medial epicondyle with the knee at 30° of flexion. That same single femoral tunnel will be shared by the two strands of the semitendinosus graft and a limb of gracilis autograft to reproduce the POL, passed through a tibial tunnel in the posteromedial margin of medial tibial condyle, and fixed in extension. Discussion/Conclusion: As recent evidence suggests that medial reconstruction should be preferred over repair, due to favorable complication and failure rates, we describe a technique that is both anatomic-based, reproducing the 2 main medial knee structures (sMCL, POL), and also cost-saving, with decreased need of fixation devices. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.